Comparison of the Volatility of Stock Market İndexes of Developed and Developing Economies - Ayush Yuvraj (International Journal of Advanced Science and Technology, 2020)
Volatility of a stock market index is the statistical measure of the dispersion of returns over the given time period. In general it is an assumption that the higher the volatility of the index more, risky is the investment. This means that the investment of the investors can either increase significantly or it can diminish drastically. Therefore, the research presented in this paper is an effort to study the volatility change in the indexes of stock market of developing and developing economies on the price levels. At the same time, it also becomes imperative to define a developed economy and developing economy. This paper henceforth contains the EGARCH analysis of five developed and five developing economies.